Experimental Approach for Complex Optical Fiber Angular Orientation and Twist Measurement. Issue 1 (22nd October 2021) - Idrisov, Ravil; Baghdasaryan, Tigran; Rothhardt, Manfred; Geernaert, Thomas; Bartelt, Hartmut
Abstract : Applications associated with complex, structured optical fibers having no circular symmetry often require information about their specific angular orientation. Such cases include, for example, splicing, sophisticated mode coupling, selective fiber Bragg gratings inscription, or direction‐sensitive sensing. Besides the external angular orientation of the fiber, additionally an intrinsic twist of the internal fiber structure has been identified as a critical parameter for applications. Such an intrinsic fiber twist might occur as a side effect of the fiber drawing process, or it may have been introduced intentionally as a special fiber property. In all such cases, a measurement of the local orientation along the fiber is highly desirable. A method for such measurements based on the analysis of the refractive–diffractive scattering patterns is presented. By comparing such measured patterns with reference patterns from modeling or from reference measurements, the orientation of the fiber can be identified with high accuracy and without measuring or reconstructing the detailed cross section of a fiber. The method, therefore, provides an approach for quick identification of a local angular fiber orientation status. Abstract : The measurement of angular orientation and an intrinsic twist of complex optical fibers are achieved by the analysis of scattering patterns. A correlation coefficient between a reference pattern and a measured scattering pattern is used for identifying a specific multicore fiber orientation. Both the algorithm and the optical setup are simple and can be applied during a fiber drawing procedure.